Antimicrobial, Antioxidant Activities, Phytochemical Evaluation and GC-MS Profiling of Madhuca longifolia Bark Extracts - Dhoubhadel, Kusum Maiya; Bom, Shyam; Pokherel, Krishna; Rajbhandari, Meena (Amrit Research Journal, 2023)
Madhuca longifolia, locally known as Mahua is a large to medium sized tree grows in Tarai region of Nepal. It is a medicinal plant of high economic value. Almost all parts of the plant are used by the indigenous people to cure various diseases. The bark is used to treat diabetes, cuts, wounds, itching and bleeding gums. The scientific reports about the phytochemical analysis on the bark of M. longifolia is very limited. Here we report about the extraction based on solvent polarities, chemical screening of extracts, estimation of phenolics, flavonoids, gallotannins, condensed tannins and sugars in different extracts, their antioxidant and antibacterial activities as well as GC-MS profiling of hexane extract. In our findings, ethyl acetate, methanol and 50% aqueous methanol extracts showed the presence of most of the phytochemicals like terpenoids, phenolics, flavonoids, tannins and glycosides. The greater amounts of phenolics (196±15.28 mg gallic acid equivalent, GAE/g extract), flavonoids (975±13.31 mg catechin equivalent, CE/g extract), condensed tannins (980±10.75 CE/g extract) and sugars (126±8.83 mg glucose equivalent, GE/g extract) were detected in the methanol extract, greater amounts of gallotannins were detected in the ethyl acetate extract (126±8.83 mg tannic acid equivalent, TAE/g extract). In DPPH radical scavenging assay, methanol extract showed strong radical scavenging activity with an IC50 value of 18.86 ± 1.07µg/mL. In antibacterial assay, ethyl acetate, methanol and 50% aqueous methanol extracts showed activity against S. aureus and E. coli with the inhibition zone ranged from 15-22 mm. GC-MS analysis of hexane extract showed the presence of more than nine compounds and squalene, β-amyron, β-amyrin acetate, lupeol, lupeol acetate and cis-3,14-Clerodadien-13-ol were tentatively identified by comparing mass fragmentation patterns with the standard NIST database. The finding of this study indicated that M. longifolia bark extracts can be used as a natural source of antioxidant, antibacterials and anti-inflammatory agents and supports its traditional use.